Kegiatan LDKO (Latihan Dasar Kepemimpinan OSIS) untuk Meningkatkan Kedisplinan Siswa di MAN Sidoarjo - Firdausi, Kharisma Syifanaya; Yunusi, Muhammad Yusron Maulana El; Abror, Sirojuddin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
The Student Leadership Basic Training (LDKO) program at MAN Sidoarjo was conducted as a character-building initiative to strengthen students’ discipline and responsibility through experiential learning. Discipline in the educational context extends beyond mere compliance with school rules; it involves self-regulation, time management, and alignment of behavior with moral and social values. This study employed the Participatory Action Research (PAR) method combined with a quantitative descriptive approach to measure the effectiveness of LDKO in improving student discipline. Data were collected through questionnaires, observations, and interviews involving 56 participants, evaluated based on five key indicators: punctuality, compliance with school regulations, neat appearance, responsibility in completing tasks, and teamwork. The findings revealed an overall increase in discipline scores from 2.50 to 3.54, with an average improvement of 1.04 points. The highest improvement was observed in teamwork, followed by responsibility and adherence to rules. These results suggest that LDKO effectively fosters disciplined behavior through leadership training, structured activities, and reflective learning. Furthermore, the program encourages the development of participatory and sustainable leadership among students within the school environment.